SRSF9 selectively represses ADAR2-mediated editing of brain-specific sites in primates - Zhang, Fan (2019)
Adenosine-to-inosine (A-to-I) RNA editing displays diverse spatial patterns across different tissues. However, the human genome encodes only two catalytically active editing enzymes (ADAR1 and ADAR2), suggesting that other regulatory factors help shape the editing landscape. Here, we show that the splicing factor SRSF9 selectively controls the editing of many brain-specific sites in primates. SRSF9 is more lowly expressed in the brain than in non-brain tissues. Gene perturbation experiments and minigene analysis of candidate sites demonstrated that SRSF9 could robustly repress A-to-I editing by ADAR2. We found that SRSF9 biochemically interacted with ADAR2 in the nucleus via its RRM2 domain. This interaction required the presence of the RNA substrate and disrupted the formation of ADAR2 dimers. Transcriptome-wide location analysis and RNA sequencing revealed 1328 editing sites that are controlled directly by SRSF9. This regulon is significantly enriched for brain-specific sites. We further uncovered a novel motif in the ADAR2-dependent SRSF9 binding sites and provided evidence that the splicing factor prevents loss of cell viability by inhibiting ADAR2-mediated editing of genes involved in proteostasis, energy metabolism, the cell cycle and DNA repair. Collectively, our results highlight the importance of SRSF9 as an editing regulator and suggest potential roles for other splicing factors.